The Rise and Fall of Modern Plagues - G. Terry Sharrer (Molecular Frontiers Journal, 2020)
Millennia separate smallpox, the oldest pandemic, and COVID-19, the newest. Both calamities arose from an opportunistic virus amid human crowding. A vaccine for smallpox existed since the late 18th century, but it took worldwide public health strategy to eradicate it. COVID-19 proceeds against a hive of scientific collaboration, but succeeds, so far, from weak containment policies. COVID-19 was first identified in China, but it rose to become the American pandemic.